Extreme measures : [compact disc, unabridged] : a thriller - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2008)
A faithful servant of his country for 16 years, first as a Marine and then as a member of the elite counterterrorism unit, Mike Nash has lived up to the call of duty. However, no amount of training or service could prepare him for his own country turning on him.